PENENTUAN BATAS WILAYAH LAUT PROVINSI JAWA TENGAH DAN JAWA BARAT MENGGUNAKAN DATUM GEODESI NASIONAL - Sutomo Kahar (TEKNIK, 2013)
According to Minister of Internal Affair regulation which is Permendagri No.1 Tahun 2006, Peta LingkunganLaut Indonesia (LLN) must be utilized to define boundaries of province sea jurisdiction. Unfortunately, PetaLingkunan Laut Indonesia still applies Indonesia Datum 1974 instead of Datum Geodesi Nasional 1995. It iscontrary with Permendagri No 76 Tahun 2012 and UU No.4 Tahun 2011 which declare the urgency of singlereference datum for Indonesia region. To fit the requirement, Peta Lingkungan Laut Indonesia must betransformed into official datum. This research applied two transformation formulae. There was LaufTransformations to accomodate 2 Dimension Transformation. Computation of transformation parameters andapplication of those parameters were tested at North Coast of Java from Kendal regency to Brebes regency. Ascalculated in MatLab software, this research concluded that Lauf transformation was good for transformingLingkungan Laut Indonesia from ID74 to DGN95.